Pharmacokinetic-Pharmacodynamic Modeling of the D(2) and 5-HT(2A) Receptor Occupancy of Risperidone and Paliperidone in Rats - Kozielska, Magdalena (Springer US, 2012)
PURPOSE: A pharmacokinetic-pharmacodynamic (PK-PD) model was developed to describe the time course of brain concentration and dopamine D(2) and serotonin 5-HT(2A) receptor occupancy (RO) of the atypical antipsychotic drugs risperidone and paliperidone in rats. METHODS: A population approach was utilized to describe the PK-PD of risperidone and paliperidone using plasma and brain concentrations and D(2) and 5-HT(2A) RO data. A previously published physiology- and mechanism-based (PBPKPD) model describing brain concentrations and D(2) receptor binding in the striatum was expanded to include metabolite kinetics, active efflux from brain, and binding to 5-HT(2A) receptors in the frontal cortex. RESULTS: A two-compartment model best fit to the plasma PK profile of risperidone and paliperidone. The expanded PBPKPD model described brain concentrations and D(2) and 5-HT(2A) RO well. Inclusion of binding to 5-HT(2A) receptors was necessary to describe observed brain-to-plasma ratios accurately. Simulations showed that receptor affinity strongly influences brain-to-plasma ratio pattern. CONCLUSION: Binding to both D(2) and 5-HT(2A) receptors influences brain distribution of risperidone and paliperidone. This may stem from their high affinity for D(2) and 5-HT(2A) receptors. Receptor affinities and brain-to-plasma ratios may need to be considered before choosing the best PK-PD model for centrally active drugs.